The Neurodiversity Internship Program at Ubongo Learning, Tanzania: A Model for Promoting Inclusion in Employment - Hussein, Hussein (Indonesian Journal of Disability Studies, 2025)
The Neurodiversity Internship Program at Ubongo Edutainment is an innovative initiative to address employment barriers faced by autistic adolescents transitioning from education to the workforce. The program integrates tailored training, mentorship, and inclusive workplace practices, fostering skills development, self-advocacy, and organizational inclusion. This paper presents a comprehensive program evaluation using qualitative research involving interns, mentors, and employees. Findings underscore the program's transformative effects on participants and the organization, highlighting its potential as a scalable model for fostering inclusion in employment. Recommendations for addressing systemic barriers, leveraging culturally relevant frameworks like Ubuntu, and scaling the initiative are discussed, with broader implications for inclusivity and equity in employment.